Prevalence of HIV and associated factors among visceral leishmaniasis cases in an endemic area of Northeast Brazil - Gardenia de Oliveira Santos; Nathalia Priscila Sales de Jesus; Juliana Vasconcelos Cerqueira-Braz; Victor Santana Santos; Ligia Mara Dolce de Lemos (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION Cases of visceral leishmaniasis (VL) and HIV co-infection have increased worldwide. We investigated the prevalence of HIV and associated factors among VL patients in Sergipe state, Brazil. METHODS We conducted a population-based study of all cases of VL and HIV reported in Sergipe from 1999 to 2015. RESULTS We studied a total of 917 patients; 41 (4.5%) co-infection cases were detected. VL-HIV co-infected patients were more likely to have weight loss, cough, treatment failure or loss to follow-up and death. CONCLUSIONS The prevalence of VL-HIV co-infection was high and co-infected patients were more likely to have adverse outcomes.